Synthesis of Organic Compounds Containing Phosphorus Using Ultra sounds - Simulescu, Vasile; Ilia, Gheorghe; C. Crasmareanu, Eleonora (Mini-Reviews in Organic Chemistry, 2016)
The technique involving ultrasound is a very modern and versatile method used in the last decades for the synthesis of organic compounds containing phosphorus. The use of ultrasonication in phosphorus chemistry was described in many scientific papers in last years. Nowadays this method is still developing. Until now, it was used for transesterification reactions, coupling reaction, production of nanocomposites, synthesis of different compounds for anticorrosion coatings, synthesis of polycyclic phosphonate resins and so on. This technique is of great interest, because first of all, it is a green method. As we will describe further in this review, in some cases the ultrasonication also improved the products yield, in comparison with the classical approaches.
Keywords: Green chemistry